Antibacterial Properties of Plasma-Activated Perfluorinated Substrates with Silver Nanoclusters Deposition - Slepička, Petr; Rimpelová, Silvie; Slepičková Kasálková, Nikola; Fajstavr, Dominik; Sajdl, Petr; Kolská, Zdeňka; Švorčík, Václav (Nanomaterials (Basel, Switzerland), 2021)
This article is focused on the evaluation of surface properties of polytetrafluoroethylene (PTFE) nanotextile and a tetrafluoroethylene-perfluoro(alkoxy vinyl ether) (PFA) film and their surface activation with argon plasma treatment followed with silver nanoclusters deposition. Samples were subjected to plasma modification for a different time exposure, silver deposition for different time periods, or their combination. As an alternative approach, the foils were coated with poly-L-lactic acid (PLLA) and silver. The following methods were used to study the surface properties of the polymers: goniometry, atomic force microscopy, and X-ray photoelectron microscopy. By combining the aforementioned methods for material surface modification, substrates with antibacterial properties eliminating the growth of Gram-positive and Gram-negative bacteria were prepared. Studies of antimicrobial activity showed that PTFE plasma-modified samples coated with PLLA and deposited with a thin layer of Ag had a strong antimicrobial effect, which was also observed for the PFA material against the bacterial strain of S. aureus. Significant antibacterial effect against S. aureus, Proteus sp. and E. coli has been demonstrated on PTFE nanotextile plasma-treated for 240 s, coated with PLLA, and subsequently sputtered with thin Ag layer.
Keywords: fluorinated ethylene propylene; nanostructured surface; poly(L-lactic) acid; material morphology; plasma treatment; antibacterial properties; polytetrafluoroethylene; silver nanoclusters